Dose-Dependent Effects of GLD-2 and GLD-1 on Germline Differentiation and Dedifferentiation in the Absence of PUF-8 - Park, Youngyong; O’Rourke, Samuel; Taki, Faten A.; Alfhili, Mohammad A.; Lee, Myon Hee (Frontiers in Cell and Developmental Biology, 2020)
PUMILIO/FBF (PUF) proteins have a conserved function in stem cell regulation. C. elegans PUF-8 protein inhibits the translation of target mRNAs by interacting with PUF binding element (PBE) in the 3’ untranslated region (3’ UTR). In this work, an in silico analysis has identified gld-2 (a poly(A) polymerase) as a putative PUF-8 target. Biochemical and reporter analyses showed that PUF-8 specifically binds to a PBE in gld-2 3’ UTR and represses a GFP reporter gene carrying gld-2 3’ UTR in the C. elegans mitotic germ cells. GLD-2 enhances meiotic entry at least in part by activating GLD-1 (a KH motif-containing RNA-binding protein). Our genetic analyses also demonstrated that heterozygous gld-2(+/-) gld-1(+/-) genes in the absence of PUF-8 are competent for meiotic entry (early differentiation), but haplo-insufficient for the meiotic division (terminal differentiation) of spermatocytes. Indeed, the arrested spermatocytes return to mitotic cells via dedifferentiation, which results in germline tumors. Since these regulators are broadly conserved, we thus suggest that similar molecular mechanisms may control differentiation, dedifferentiation, and tumorigenesis in other organisms, including humans.